2020
DOI: 10.1038/s41467-020-19837-z
|View full text |Cite
|
Sign up to set email alerts
|

A grass-specific cellulose–xylan interaction dominates in sorghum secondary cell walls

Abstract: Sorghum (Sorghum bicolor L. Moench) is a promising source of lignocellulosic biomass for the production of renewable fuels and chemicals, as well as for forage. Understanding secondary cell wall architecture is key to understanding recalcitrance i.e. identifying features which prevent the efficient conversion of complex biomass to simple carbon units. Here, we use multi-dimensional magic angle spinning solid-state NMR to characterize the sorghum secondary cell wall. We show that xylan is mainly in a three-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 68 publications
(143 reference statements)
2
60
0
Order By: Relevance
“…It was suggested that grass xylan may have side-chain decorations incompatible with binding to cellulose in the Xn 2f conformation and that this Xn 2f conformation may arise only after dehydration. 37 The present study on never-dried Brachypodium tissues confirms that some xylan in grasses does indeed have branches that permit binding to cellulose in the Xn 2f conformation. 16 …”
Section: Discussionsupporting
confidence: 73%
“…It was suggested that grass xylan may have side-chain decorations incompatible with binding to cellulose in the Xn 2f conformation and that this Xn 2f conformation may arise only after dehydration. 37 The present study on never-dried Brachypodium tissues confirms that some xylan in grasses does indeed have branches that permit binding to cellulose in the Xn 2f conformation. 16 …”
Section: Discussionsupporting
confidence: 73%
“…Recently, it was reported that xylan Ara f signals in an INADEQUATE experiment were reduced by lyophilization and rehydration of sorghum. 58 …”
Section: Resultsmentioning
confidence: 99%
“…For instance, EC 3.2.1.4 (cellulases) and EC 3.2.1.8 (xylanases) both occurred in at least 8 different homologous superfamilies. Cellulose, as the most abundant polysaccharide on Earth, and hemicellulose with xylan as the main component together constitute plant cell wall material [45] , [46] . Therefore, we speculate that the large biomass and high degradation difficulty might be the reasons for the widespread multiorigin convergent evolution of the degradation activities of polysaccharides.…”
Section: Discussionmentioning
confidence: 99%